Histories of Hating. (8th September 2015) - Shepherd, Tamara; Harvey, Alison; Jordan, Tim; Srauy, Sam; Miltner, Kate
This roundtable discussion presents a dialogue between digital culture scholars on the seemingly increased presence of hating and hate speech online. Revolving primarily around the recent #GamerGate campaign of intensely misogynistic discourse aimed at women in video games, the discussion suggests that the current moment for hate online needs to be situated historically. From the perspective of intersecting cultural histories of hate speech, discrimination, and networked communication, we interrogate the ontological specificity of online hating before going on to explore potential responses to the harmful consequences of hateful speech. Finally, a research agenda for furthering the historical understandings of contemporary online hating is suggested in order to address the urgent need for scholarly interventions into the exclusionary cultures of networked media.